2010
DOI: 10.14238/pi50.3.2010.149-53
|View full text |Cite
|
Sign up to set email alerts
|

Mortality predictors of pneumonia in children

Abstract: Background Pneumonia is one of the main causes of death in children in developing countries. It is important to identify clinical signs, demographic factors, and laboratory data which can be used to predict children who have higher risk of mortality from pneumonia.Objective To find the clinical signs, demographic factors and laboratory data that can be used as predictors of mortality from pneumonia.Methods T his historical case􀀽control study was carried out in Sardjito Hospital between January 2004 and Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 0 publications
0
13
0
2
Order By: Relevance
“…Hal ini dijelaskan bahwa anak di bawah usia 1 tahun memiliki saluran napas yang lebih sempit sehingga akan mudah menderita infeksi saluran pernapasan seperti pneumonia dan bila area yang terkena peradangan bertambah luas akan menyebabkakan risiko terjadinya obstruksi saluran pernapasan dan meningkatkan kejadian hipoksia. 11 Penelitian di negara Zambia dinyatakan bahwa pneumonia merupakan penyebab utama kesakitan pada anak di bawah usia 5 tahun, 12 hal ini dapat terjadi karena pada usia tersebut anak balita sudah mulai mengetahui lingkungan untuk bermain di luar rumah sehingga akan mudah terpapar oleh agen penyebab pneumonia dan didukung oleh respons imunitas yang belum berkembang dengan baik. 5 Jenis kelamin anak balita yang datang untuk berobat ke UPT Puskesmas Ibrahim Aji didominasi oleh balita laki-laki sebanyak 59% bila dibandingkan dengan perempuan sebanyak 41%.…”
Section: Pembahasanunclassified
“…Hal ini dijelaskan bahwa anak di bawah usia 1 tahun memiliki saluran napas yang lebih sempit sehingga akan mudah menderita infeksi saluran pernapasan seperti pneumonia dan bila area yang terkena peradangan bertambah luas akan menyebabkakan risiko terjadinya obstruksi saluran pernapasan dan meningkatkan kejadian hipoksia. 11 Penelitian di negara Zambia dinyatakan bahwa pneumonia merupakan penyebab utama kesakitan pada anak di bawah usia 5 tahun, 12 hal ini dapat terjadi karena pada usia tersebut anak balita sudah mulai mengetahui lingkungan untuk bermain di luar rumah sehingga akan mudah terpapar oleh agen penyebab pneumonia dan didukung oleh respons imunitas yang belum berkembang dengan baik. 5 Jenis kelamin anak balita yang datang untuk berobat ke UPT Puskesmas Ibrahim Aji didominasi oleh balita laki-laki sebanyak 59% bila dibandingkan dengan perempuan sebanyak 41%.…”
Section: Pembahasanunclassified
“…10 The most common nutritional status of our subjects was undernourished (53.49%). In contrast, Kisworini et al 8 and Beyeng et al 9 found more pneumonia patients in the well-nourished category with 69% and 51.1%, respectively. Sensitivity, specificity, positive predictive value and negative predictive value were different from those reported by Moreno et al, 5 who examined the development and validation of clinical predictors for distinguishing bacterial and viral pneumonia in children.…”
Section: Resultsmentioning
confidence: 88%
“…This result was different from that obtained by Kisworini et al, who examined clinical symptoms, laboratory and demographic data as predictors of mortality in children with pneumonia and Beyeng et al, who examined BPS validity as a predictor of pneumonia bacteremia in children. Kisworini et al 8 and Beyeng et al 9 found the average ages of their sample who suffered from pneumonia, to be 16 month and 11 months, respectively. However, Torres et al, who examined the clinical predictors for initial treatment our hospital criteria: fever, cough, shortness of breath (based on age according to WHO), 7 respiratory distress (or nasal flaring and grunting and/or suprasternal/ intercostal/subcostal retractions), and smooth wet loud rales on chest auscultation.…”
Section: Discussionmentioning
confidence: 93%
“…This result was similar to studies by Kisworini P et al and Beyeng et al which had mean subject ages of 16 and 11 months, respectively. 13,14 The peak 70%, respectively). Another study also reported that procalcitonin (cut-off point 0.25 ng/mL) had higher diagnostic accuracy than that of CRP and that total leukocytes can differ between community-acquired pneumonia and infection cause.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, Kisworini et al and Beyeng et al had more boys than girls in their studies, with 55% and 59.4%, respectively. 13,14 Our largest subject age group was under five years (99%), with children aged 2-11 months comprising 46%, and those aged 1-4 years comprising 53%. This result was similar to studies by Kisworini P et al and Beyeng et al which had mean subject ages of 16 and 11 months, respectively.…”
Section: Discussionmentioning
confidence: 98%